Peningkatan Penguasaan Materi Hadits melalui Metode Resitasi pada Mahasiswa PAI FTK UIN Ar-Raniry - Bachtiar Ismail; Ismail Darimi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
The crises of Arabic writing skills, reading, translating and understanding Hadith text by students became the basis of this research. The objective provides an overview of improving rote learning, writing hadith and interpretation of hadiths on students of Islamic Education Studies Program. The type of research is action research conducted through four main steps namely planning, action, observation, and reflection. Method of data settlement in this research that is observation note, daily journal and result of evaluation which done from beginning of research (pre test) until last cycle. Data analysis techniques used are flow model: data reduction, data presentation and withdrawal. The results showed that the regression method can improve the competence of memorization, write the hadith and interpretation of hadith on the students of Islamic Education Study Program. Each increase, the completeness in the last cycle with the average value is 67.06 is already more than the maximum predetermined criteria that is 65. Recitation learning method can increase the interpretation of hadith values ​​in the students of Islamic Education Studies program. Students can interpret the hadith with Intercontextual Interpretation technique